Insecticidal Effect of a Natural Turkish Diatomaceous Earth Formulation on Greater Wax Moth - Mustafa Güneşdoğdu; Ali Bayram; Ali Arda Işıkber; Ahmet Şekeroğlu; Hüseyin Bozkurt (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the insecticidal effect of the Detech® (Turkish Diatomaceous earth) DE formulation against Galleria mellonella L. was determined. The study was conducted in a laboratory environment with materials taken from beehives produced at Muş Alparslan University in 2022. Diatomaceous earth (DE) was applied in two different forms (dust and slurry DE) and as positive control GüveSavar®, which is currently used against some pests in beekeeping. DE concentrations of 0, 3, 5, and 7 g/m2 in different exposure times were tested for the control of G. mellonella larvae. As a result of all treatments, the highest mortality occurred at 7 g/m2 dust DE concentration. Larvae (3rd stage) exposed to 7 g/m2 concentration according to dust DE mortality rates reached 100% mortality after 40 hours. According to the results of the slurry DE, the larvae exposed to the slurry diatom at all concentrations achieved 100% mortality at the end of the 96 hours. When the dust and slurry DE results were examined, the direct use of dust formulations greatly accelerated the effectiveness against larvae. The study showed very promising results, suggesting that slurry DE and dust formulations could be a new alternative control method for Greater Wax Moth. In addition, for the first time, the insecticidal efficacy of DE against the honey bee pest, the greater wax moth, was determined.